Analisis Kesulitan Guru Menerapkan Teknologi Dalam Proses Pembelajaran di SD Negeri 08 Bilah Hilir Labuhan Batu T.A 2022/2023 - Citra Anjelina Lumban Gaol; Sorta Simanjuntak (Departement of Mathematics Education, 2023)
The problem in this study is the difficulty the teachers at SD Negeri 08 Bilah Hilir Labuhan Batu T.A 2022/2023 have in implementing technology to the learning process. The purpose of this study is to determine how challenging it is for teachers to implement technology-based learning and what factors instructors face when implementing technology-based learning.This study is a descriptive quantitative study. This study's sample consisted of 32 respondents from SD Negeri 08 Bilah Hilir. The questionnaire method is used to collect data, with the Guttman scale serving as the research instrument. Descriptive analysis with a quantitative approach is employed for data analysis.The difficulty for teachers in implementing technology-based learning is due to the lowest indicator of the age factor; there are older teachers; it is difficult to apply technology in learning with a percentage of 37.5% in the sufficient category, supported by respondents from students with school facilities indicators as high as 40.17 % in the sufficient category, so the required facilities are not met. Thus, it was determined that teachers at SD Negeri 08 Bilah Hilir Labuhan Batu T.A 2022/2023 had sufficient difficulties applying technology in the learning process, but could still apply technology-based learning, which was supported by the highest percentage of indicators.